Portfolio Choice When Managers Control Returns - Egil Matsen (Norges Bank, 2005)
This paper investigates the allocation decision of an investor with two projects. Separate managers control the mean return from each project, and the investor may or may not observe the managers' actions. We show that the investor's risk-return trade-off may be radically different from a standard portfolio choice setting, even if managers' actions are observable and enforceable. In particular, feedback effects working through optimal contracts and effort levels imply that expected terminal wealth is nonlinear in initial wealth allocation. The optimal portfolio may involve very little diversification, despite projects that are highly symmetric in the underlying model. We also show that moral hazard in one of the projects need not imply lower allocation to that project. Expected returns are generally lower than under the first-best, but the optimal contract shifts more of the idiosyncratic risk in the hidden action project to the manager in charge of it. The minimum-variance position of the investor's (net) terminal wealth would in most cases involve a portfolio shift towards the hidden action project, and there are plausible cases where this would dominate the overall effect on the second-best optimal portfolio when comparing with the first-best.
hdl:11250/2498433
Keywords: D81; D82; G11; 330; portfolio choice; diversification; optimal contracts